Reading Descartes Otherwise : Blind, Mad, Dreamy, and Bad - Lee, Kyoo (Fordham University Press, 2012)
Focusing on the first four images of the Other mobilized in Descartes' Meditations - namely, the blind, the mad, the dreamy, and the bad - this book casts light on what have heretofore been the phenomenological shadows of "Cartesian rationality." In doing so, it discovers dynamic signs of spectral alterity lodged both at the core and on the edges of modern Cartesian subjectivity